Growth, development, survival and settlement rate of sandfish (Halothuria scabra) larvae reared using different microalgae and settlement cues - Sibonga, Rema Cajilig (2017.)
Growth, development and survival of Holothuria scabra larvae fed with different microalgae were studied. In the first experiment, chaetoceros calcitrans, Rhodomonas sp. a,d Tetraselmis tetrahele at 10000, 20000, 30000 and 40000 cells ml-1 had the highest mean body length (BL) at late auricularia (1032.41+38.70 um). However, those fed with C. calcitrans at 20000 cells ml-1 showed higher daily growth rate (DGR) of 31.4+5.2 um d-1. Development to 50% competent larvae was shorter using C. calcitrans at 20000 and 30000 cells ml-1. At 12 days post-fertilization (DPF), larvae fed with c. calcitrans at 20000 and 40000 cells ml-1 showed significantly higher % doliolaria (p<0.05) and those fed at 20000 cells ml-1 showed highest survival of 53% at 14 DPF. In the second experiment, three combinations of microalgae contining 10000 cells ml-1 of each microlaga were used : C. calcitrans and Rhodomonas sp., C. calcitrans and T. Tetrahele, and Rhodomonas sp. and T. tetrahele. Larvae fed with mixed c. calcitrans and Rhodomonas sp. showed significantly higher mean BL at late auricularia (991.0+15.8 um) and DGR (43.8+9.9 um d-l) (p<0.05). Larvae showed faster development and higher survival of 86% at 10 DPF. In summary, C. calcitrans at 20000 cells ml-1 is recommended as a single diet while a combination of C. calcitrnas and Rhodomonas sp. as a mixed diet. Settlement of H. scabra on substrates with different cues was also investigated using corrugated plastic sheets (CPS) as substrate and Navicula, c. calcitrans paste and Spirulina paste as cues.. CPS without cue served as control. Although no significant differences, Spirulina paste showed highest settlement rate (88.54%) followed by Navicula and C. calcitrans paste. Control showed significantly lowest settlement rate. Therefore, spirulina paste best induced settlement of H. scabra. However, Navicula and c. calcitrans pate may be used as cheaper settlement cue substitutes.
Thesis (M.S. Fisheries-Aquaculture) -- Miagao, Iloilo : Institute of Aquaculture, College of Fisheries and Ocean Sciences, University of the Philippines Visayas, July 2017.
Keywords: Sandfish; Halothuria scabra; Microalgae; Settlement cues